Contemporary Educational Interventions for General Practitioners (GPs) in Primary Care Settings in Australia: A Systematic Literature Review - Bernardes, Christina Maresch; Ratnasekera, Isanka Umayangani; Kwon, Joo Hyun; Somasundaram, Sivagowri; Mitchell, Geoff; Shahid, Shaouli; Meiklejohn, Judith; O'Beirne, James; Valery, Patricia Casarolli; Powell, Elizabeth (Frontiers in Public Health, 2019)
Background: The primary purpose of educational interventions is to optimise the clinical management of patients. General practitioners (GPs) play a major role in the detection and management of diseases. This systematic literature review will describe the type and outcomes of educational interventions designed for general practitioners (GPs) in the Australian context. Methods: PubMed, CINHAL, and Scopus databases were systematically searched for studies on educational interventions conducted for GPs in Australia during 1st January 2008 to 11th June 2018. Data collected on the methodology of the interventions, GPs satisfaction regarding the educational intervention, changes in knowledge, confidence, skills and clinical behaviour of the GPs. We also assessed whether the acquired clinical competencies had an impact on organizational change and on patient health. Results: Thirteen publications were included in this review. The methods with which educational interventions were developed and implemented varied substantially and rigorous evaluation was generally lacking particularly in detailing the outcomes. The reported GP response rate varied between 2% to 96% across studies, depending upon the method of recruitment, the type of intervention and the study setting (rural vs. urban). The most effective recruitment strategy was a combination of initial contact coupled with a visit to GP practices. Nine of the studies reviewed reported improvement in at least one outcome measure: gaining knowledge, improving skills or change in clinical behaviour which was translated into clinical practice. In the 3 pre- and post-intervention analysis studies, 90-100% of the participating GPs reported improvement in their knowledge and attitudes. Conclusion: Education interventions for GPs in Australia had low response (recruitment) and retention (GPs that participated in follow-ups) rates, even when financial benefits or CPD points were used as incentives. Higher GP response rates were achieved through multiple recruitment strategies. Multifaceted interventions were more likely to achieve the primary outcome by improving knowledge, skills or changing practice, but the effect was often modest. Inconsistent results were reported in studies involving the use of multiple contact methods within an intervention and conducting online interventions.